Frontal Ostium Grade (FOG): A New Computer Tomography Grading System for Endoscopic Frontal Sinus Surgery. (5th May 2020) - Gheriani, Heitham; Al‐Salman, Rami; Habib, Al‐Rahim R.; Javer, Amin
Abstract : Objective: The location and size of the frontal sinus ostium are critical in determining surgical difficulty. The more anterior the ostium, the more difficult is the surgical access. We propose a novel computed tomography (CT) grading specific to the anatomical position of the frontal ostium. Study Design: Observational study followed by a prospective part. Settings: Tertiary rhinology practice Subject and Methods: On a specified sagittal CT cut, a vertical line was drawn through the posterior edge of the frontal process of the maxilla (frontal buttress/beak) along its vertical axis (reference [R‐] line). A second (S‐) line was placed at the point of upturn of the skull base. Based on if the S‐line was posterior or anterior to the R‐line, the frontal ostium was graded positive and more easily accessible or negative and thereby more challenging, respectively. If both lines overlapped, then a neutral (0) grading existed. Results: A total of 297 CTs (594 ostia) were analyzed. In total, 394 (65%) ostia were grade positive, 52 (8.75%) were grade negative, and 103 (17.3%) were grade neutral. Ninety frontal sinusotomies were then performed using this grading system: 48 were positive, 21 negative, and 21 neutral. The average time to complete a frontal sinusotomy was 9.96 minutes for grade positive compared to 11.4 minutes for neutral and 16.05 minutes for grade negative ( P <. 005). Conclusion: This novel anatomical CT grading system is designed to be useful in planning and predicting the level of difficulty in endoscopic frontal sinus surgery.